THE ROLE OF THE INDONESIA-PAPUA NEW GUINEA BORDER IN PREVENTING THE SPREAD OF COVID-19 - Korwa, Johni R.V.; Sinaga, Melpayanty (Jurnal Penelitian Politik, 2021)
This paper aims to examine the extent to which the Indonesia-Papua New Guinea (PNG) border has played a role in preventing the spread of Covid-19. This case study demonstrates an example of how two countries cooperate with one another in times of the Covid-19 pandemic. The research method used to analyze the topic adopts a qualitative descriptive approach. This paper finds out that the Indonesia-PNG border has not only acted as a deterrent, but it has also ensured human security and facilitated repatriation in the midst of Covid-19. Even though PNG has perceived Indonesia as a threat due to the increasing number of Covid-19 cases in Papua province, the cooperation between the two countries remains strong. Moreover, protecting human security in the borders of Indonesia and PNG is vitally important in times of Covid-19. The two countries have ensured the closing of the border areas in January 2020 as well as the deployment of security forces along the borders. Both nations have also successfully implemented repatriation of their citizens from PNG to Indonesia and vice versa through PLBN (Cross-Border Post) in Skouw, Jayapura. The case study demonstrates how the high number of recorded cases of Covid-19 in Indonesia has not resulted in transfers of the virus over the PNG border. Keywords: Covid-19, Indonesia, PNG, human security, PLBN, Regional  Border